Yield gap of rice in Alappuzha district of Kerala - Job, Elsamma (Journal of Tropical Agriculture, 2007)
To evaluate the gap between maximum feasible and actual yields obtained by rice (Oryza sativa) farmers of Alappuzha, a study was conducted adopting a three stage random sampling scheme. Frontier production function was used to estimate the maximum feasible yield (MFY) and yield gap. Rice yield gap in Alappuzha was estimated as 1588 kg ha-1 with an MFY of 5447 kg and actual yield of 3859 kg ha-1 implying the occurrence of certain constraints in raising productivity at the farm-level.